Methods of decreasing the level of crime rate through the design of an urban environment - Butabekova A., Butabekova A.; Kassymova A., Kassymova A. (Рroblems of engineering and professional education, 2023)
The article analyzes the laws used in designingpublic spaces and roads, new scientific discoveries, the results of their development in real life and the degree of their development. The person as the best instrument of observation and the main point in the concept of safe space.